3
$\begingroup$

My task is to check whether the series $$\sum_{n=1}^\infty {\frac{(-2)^n+n^2}{n2^n}}$$ converges or not. So I tried expanding the fraction like that(should equal to original form): $$\sum_{n=1}^\infty {(-1)^n\frac{2^n}{n2^n}+\frac{n^2}{n2^n}}=\sum_{n=1}^\infty {(-1)^n\frac{1}{n}+\frac{n}{2^n}}$$

Then I thought about that the first addend does converge because of Leibniz's rule and the second addend converges because $2^n$ grows much faster than $n$.

But I'm not sure(and rather thinking this form of argumentation is wrong) if I can take addends of a series and prove convergence for each addend instead of proving convergence for the whole series.


I would appreciate if someone can point me to the right direction.

$\endgroup$
5
  • $\begingroup$ You are using as an upper limit the "dummy index" $n$. $\endgroup$
    – Mark Viola
    Dec 1, 2015 at 4:50
  • 2
    $\begingroup$ It is a theorem that if $\sum_0^\infty a_n$ and $\sum_0^\infty b_n$ converge, then $\sum_0^\infty (a_n+b_n)$ converges. $\endgroup$ Dec 1, 2015 at 4:50
  • $\begingroup$ @Dr.MV thank you, corrected it, it should be infinty $\endgroup$ Dec 1, 2015 at 4:55
  • $\begingroup$ You're welcome. My pleasure. And @AndréNicolas has answered the question. Are you good to go now? $\endgroup$
    – Mark Viola
    Dec 1, 2015 at 4:57
  • $\begingroup$ Yep, good to go now :) $\endgroup$ Dec 1, 2015 at 4:59

2 Answers 2

2
$\begingroup$

The 1st one is $-\ln 2$ (Taylor series).

The 2nd one is $$f(x)=\sum_{n=1}^{\infty}n\cdot x^n$$ $$\int \frac{f(x)}{x}dx=\sum_{n=1}^{\infty}x^n=\frac{x}{1-x}$$ $$\therefore f(x)=x\cdot\left(\frac{x}{1-x}\right)'=\frac{x}{(1-x)^2}$$ $$\sum_{n=1}^{\infty}n\cdot\left(\frac12\right)^n=\frac{\frac12}{(1-\frac12)^2}=2$$ So the total sum is $2-\ln2$.

$\endgroup$
2
$\begingroup$

To control if the series: $$\sum_{n=1}^\infty {(-1)^n\frac{1}{n}+\frac{n}{2^n}}$$ you can use the Leibniz's rule. First you have to demonstrate that $$-\frac {1}{n}+\frac {n}{2^n}<0$$ for every $n$. Indeed you can note that rewriting the expression $$-\frac {2^n+n^2}{n\cdot 2^n}<0$$. Therefore now you know that for $n\to \infty$ $$ \frac {1}{n}+\frac {n}{2^n}\to 0$$ therefore you have to demonstrate $$\frac {1}{n}+\frac {n}{2^n}$$ is decreasing proving that the derivate of $f(x)=\frac {1}{x}+\frac {x}{2^x}<0$ after a value of $x$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.